The role of perceived organisational support on technostress and work–family conflict - Chenè E. Ward; Martha Harunavamwe (SA Journal of Industrial Psychology)
Orientation: The role of workplace support has been well established; however, with tech-driven hybrid work settings, technostress makes managing work-family conflict daunting for employees.